Quo Vadis Traditional Cultural Expressions Protection: Threats from Personal Intellectual Property and Artificial Intelligence - Dharmawan, Ni Ketut Supasti; Kasih, Desak Putu Dewi; Samsithawrati, Putu Aras; Dwijayanthi, Putri Triari; Salain, Made Suksma Prijandhini Devi; Mahaswari, Mirah; Ustriyana, Made Grazia; Moisa, Robert Vaisile (LAW REFORM, 2023)
Legal certainty for Communal Intellectual Property protection on the inventory and record-keeping arrangements in terms of ownership proof in Indonesia, has increasingly been regulated in various regulations. However, threats are also growing. Traditional Cultural expression works are easily turned into personal video works. Along with that, such works are also vulnerable as those are easily threatened by Artificial intelligence’s ability to express works made from previous works of art such as paintings. This article aims to analyze Traditional Cultural Expressions protection which are transformed or adapted into personal works or works made by Artificial Intelligence and the measures to overcome these threats. The results show that referring to Government Regulation 56/2022, the commercial use of Traditional Cultural Expressions works both in the form of adaptation and transformation by individual humans and Artificial Intelligence is required to obtain a permit and pay attention to the distribution of benefits which will further be determined by the Minister. However, regulations on this mechanism has not been explicitly regulated. Measures to overcome threats can be made through measures to turn threats into opportunities and strengths. It is also relevant to prioritize countervailing measures, namely by following the pattern of threats as a balancing act.